Candida species isolated from cerebrospinal fluid - Dorko, E; Pilipcinec, E; Tkáciková, L (Folia microbiologica, 2002)
In the period from November 1998 to June 2001 13 cases of nosocomial meningitis were reported. Candida albicans was isolated from 54% of the patients (7); C. parapsilosis from 23% (3); C. tropicalis from 15% (2) and C. krusei from 8% (1). C. albicans was isolated from the cerebrospinal fluid (CSF) of five children with the following diagnoses: nonspecified tumor of the central nervous system, Hodgkin's disease, meningitis, suspect neuroinfection, and sepsis. Examination of CSF allowed us to detect 2 strains of C. albicans from adult patients, one after neurosurgery because of a brain tumor and one with a vascular disease of the brain. C. parapsilosis was found in CSF from two premature children and one child with epilepsy. Two isolates of C. tropicalis were obtained from both blood and the CSF of a child from the neonatal intensive care unit and from a child from pediatric oncology with multiple malignant neoplasms. Only one strain of C. krusei was found in the oral cavity and CSF of a patient after neurosurgery performed after head trauma.
Keywords: lidé; kandidóza; Adult; Middle Aged; fungální meningitida; Risk Factors; Female; dítě; Humans; Infant, Newborn; Intensive Care Units, Neonatal; mozkomíšní mok; lidé středního věku; mužské pohlaví; Candidiasis; Cerebrospinal Fluid; jednotky intenzivní péče o novorozence; novorozenec; ženské pohlaví; Meningitis, Fungal; Male; Child; dospělí; Candida; rizikové faktory